Contribution of Agriculture to Romania's Gross Domestic Product - Agatha POPESCU (Communications of International Proceedings, 2020)
The paper analyzed Romania's GDP and GDP produced in agriculture in the period 2008-2019 pointing out the changes by resources and in the territory, and also in agriculture by micro regions. Descriptive statistics, and trend regression functions, correlation and determination coefficients were used to process the data. In 2019, Romania achieved Euro 222 Billion GDP, almost double than in 2008. Trade, transportation, tourism, Industry, and Public services have the highest contribution to GDP. More than 50% of GDP is achieved by three regions: Bucharest- Ilfov, North West and South Muntenia. Agriculture carried out Euro 11.08 Billion GDP in 2019, by 55% more than in 2008 and contributes by 5% to GDP. Agriculture GDP has a more balanced growth in the territory. The dynamics from the last decade and the positive connection between GDP in agriculture and Romania's GDP (r  = 0.731), R2 = 0.534, and the regression model, Y = 19.820 x + 29.423, reflects that agriculture will continue to be an important sector of the economy in the future. If in case of GDP per capita Romania accounts for 69% of the EU-27 average (Euro 31,000), and occupying the 24th position, for GDP created in agriculture, Romania is ranked the 5th in the EU after France, Italy, Spain, and Germany. It is expected that in the future Romania's economic growth to continue and GDP produced in agriculture to increase much more.
Keywords: Agriculture; Gross Domestic Product; trends; Romania.